2022
DOI: 10.31616/asj.2021.0337
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Intravenous Nefopam for Postoperative Pain in Minimally Invasive Spine Surgery: A Randomized Prospective Study

Abstract: Randomized double-blind control study. Purpose: To evaluate the effects of nefopam on reducing morphine consumption and postoperative pain in patients undergoing minimally invasive spine surgery (MISS) and to evaluate its effects on enhanced recovery after spine surgery. Overview of Literature: Enhanced recovery after surgery (ERAS) has become a major goal for spine surgery. Multimodal pain management combining non-opioid analgesics is a key element of this. However, there is little evidence regarding the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Nefopam administration both before the skin incision and upon the completion of surgery failed to exert a discernible influence on the total morphine consumption or the intensity of post-operative pain, as indicated by a study encompassing patients undergoing open spine procedures [19]. In a similar vein, an investigation involving patients subjected to minimally invasive spine surgery unveiled that the incorporation of a 24-hour nefopam infusion did not yield any incremental analgesic benefits or lead to improved functional outcomes post-surgery [20].…”
Section: Discussionmentioning
confidence: 99%
“…Nefopam administration both before the skin incision and upon the completion of surgery failed to exert a discernible influence on the total morphine consumption or the intensity of post-operative pain, as indicated by a study encompassing patients undergoing open spine procedures [19]. In a similar vein, an investigation involving patients subjected to minimally invasive spine surgery unveiled that the incorporation of a 24-hour nefopam infusion did not yield any incremental analgesic benefits or lead to improved functional outcomes post-surgery [20].…”
Section: Discussionmentioning
confidence: 99%
“…According to a study involving patients undergoing open spine surgeries, nefopam administered before the skin incision and at the end of surgery did not yield any difference in the amount of morphine consumption and the severity of postoperative pain [ 9 ]. Similarly, a study involving patients undergoing minimally invasive spine surgery showed that the inclusion of 24-hour nefopam infusion revealed no additional analgesic effect or improved functional outcomes postoperatively [ 13 ]. To date, no evidence shows any additional advantage of nefopam in spine surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…They also found no significant difference in postoperative morphine consumption among the four groups [ 26 ]. Other studies have also shown that nefopam had no or limited efficacy on postoperative pain management when it was used as a part of multimodal analgesia [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%